DAMPAK PENERAPAN METODE MENGAJAR GURU AGAMA KATOLIK DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS VIII A DI SMP NEGERI OELNEKE KECAMATAN MUSI, KABUPATEN TIMOR TENGAH UTARA - Naif, Falentinus; Kase, Emanuel Bai Samuel; Dau, Yoseph Lodowik Deki; Siono, Yeremias (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2022)
This research was conducted to find out how the learning methods applied by Catholic religion teachers in class VIII A of SMP Negeri Oelneke and how the learning motivation of students was when faced with the application of these teaching methods. The research method used in this study is a qualitative method. Data collection techniques were carried out using observation and interviews. Data analysis techniques are carried out through data collection, data reduction, data presentation, and drawing conclusions. The results showed that the teaching methods used by Catholic religion teachers at SMP Negeri Oelneke, especially class VIII A, have so far been less varied, causing students to be less motivated to participate in learning activities. To overcome this problem, Catholic religious teachers are required to apply teaching methods that are more diverse but relevant. This means that there is a choice for teachers to use more than one teaching method as long as it can motivate students to be actively involved in the Catholic religion learning process.